Analisis Faktor-Faktor yang Mempengaruhi Pendapatan UMKM Sentra Batik di Kota Pekalongan - Yuniarum Fatin Laili; Achma Hendra Setiawan (Universitas Diponegoro, 2020)
The city of Pekalongan is well known to the public as a city with a center for batik handicrafts, where batik is one of the leading products in Pekalongan City. The purpose of this study is to analyze the factors that affect the income of SMEs Batik Center in Pekalongan City. The income of SMEs Batik Center can be influenced by various factors. This study uses capital, labor, education and working hours as independent variables. This research used primary data with questionnaire data collection method. The samples used in this study were 100 members of respondents using purposive sampling technique. The results of this research indicate positive and significant effect of capital, labor, education and working hours on the income of SMEs Batik Centers in Pekalongan City. The independent variables jointly affect the income of SMEs Batik Center in Pekalongan City by 81.5 percent. The dominant variable affecting the income of SMEs Batik Center in Pekalongan City is capital.